Analisis Fenomena Culture Shock Mahasiswa Kepulauan Riau dalam Melakukan Interaksi Sosial di Kota Yogyakarta - Rizky Amalia; Erfina Nurussa’adah (Universitas Majalengka, 2021)
Culture shock is a natural thing experienced by someone who migrates as a reaction to different cultures, environments and things that become a person's habits. This happens when someone enters and migrates to an area that has never been inhabited before, this phenomenon occurs to Riau Archipelago students who will migrate to Yogyakarta and adapt in Yogyakarta, and at first they experience anxiety, worry, and fear of the new things they will experience. face, the symptoms of culture shock that are felt cause social interaction to be hampered. This study aims to determine the phenomenon of culture shock experienced by Riau Islands students in social interaction and what efforts they make in overcoming the problem of culture shock. The method used in this study is a qualitative method using a phenomenological approach. Data collection used using observation and interview methods. This research was conducted on seven students from the Riau Islands who were in Yogyakarta. The results of the study found that there were four main problems that caused culture shock including weather factors, language, character, food, in the interaction process students from the Riau Islands were required to adapt themselves. This difference makes students from the Riau Islands experience culture shock, but to overcome this problem, students from the Riau Islands have their own way of dealing with it by increasing positive activities and conducting social interactions with their new environment.